Low-Molecular-Weight Heparin-Functionalized Chitosan-Chondroitin Sulfate Hydrogels for Controlled Release of TGF-β3 and in vitro Neocartilage Formation - Chen, You-Rong; Zhou, Zhu-Xing; Zhang, Ji-Ying; Yuan, Fu-Zhen; Xu, Bing-Bing; Guan, Jian; Han, Chao; Jiang, Dong; Yang, Yan-Yu; Yu, Jia-Kuo (Frontiers in Chemistry, 2019)
Repair of hyaline cartilage remains a huge challenge in clinic because of the avascular and aneural characteristics and the paucity of endogenous repair cells. Recently, tissue engineering technique, possessing unique capacity of repairing large tissue defects, avoiding donor complications and two-stage invasive surgical procedures, has been developed a promising therapeutic strategy for cartilage injury. In this study, we incorporated low-molecular-weight heparin (LMWH) into carboxymethyl chitosan-oxidized chondroitin sulfate (CMC-OCS) hydrogel for loading transforming growth factor-β3 (TGF-β3) as matrix of peripheral blood mesenchymal stem cells (PB-MSCs) to construct tissue-engineered cartilage. Meanwhile, three control hydrogels with or without LMWH and/or TGF-β3 were also prepared. The gelling time, microstructures, mechanical properties, degradation rate, cytotoxicity and the release of TGF-β3 of different hydrogels were investigated. In vitro experiments evaluated the tri-lineage differentiation potential of PB-MSCs, combined with the proliferation, distribution, viability, morphology and chondrogenic differentiation. Compared with non-LMWH-hydrogels, LMWH-hydrogels (LMWH-CMC-OCS-TGF-β3) have shorter gelling time, higher mechanical strength, slower degradation rate and more stable and lasting release of TGF-β3. After two weeks of culture in vitro, expression of cartilage-specific genes collagen type-2 (COL-2) and aggrecan (AGC), and secretion of glycosaminoglycan (GAG) and COL-2 proteins in LMWH-CMC-OCS-TGF-β3 group were significantly higher than those in other groups. COL-2 immunofluorescence staining showed that the proportion of COL-2 positive cells and immunofluorescence intensity in LMWH-CMC-OCS-TGF-β3 hydrogel were significantly higher than those in other groups. The LMWH-CMC-OCS-TGF-β3 hydrogel can slowly release TGF-β3 in a long term, and meanwhile the hydrogel can provide a biocompatible microenvironment for the growth and chondrogenic differentiation of PB-MSCs. Thus, LMWH functionalized CMC-OCS hydrogels proposed in this work will be beneficial for constructing functional scaffolds for tissue-engineered cartilage.